2019
DOI: 10.2217/bmm-2019-0315
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Oligomeric α-Synuclein in Reflex Tears Distinguish Parkinson'S Disease Patients From Healthy Controls

Abstract: Aim: Due to active engagement of sensory and afferent nerve fibers in reflex tearing which could be affected in Parkinson's disease (PD), we tested reflex tears as a source of potential PD biomarkers. Patients & methods: Reflex tears collected from 84 PD and 84 age- and sex-equivalent healthy controls (HC) were used to measure levels of oligomeric α-Syn (α-SynOligo), total α-Syn (α-SynTotal), CCL2, DJ-1, lactoferrin and MMP9. Results: α-synOligo (p < 0.0001), CCL2 (p = 0.003) and lactoferrin (p = 0.002)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 43 publications
0
27
0
1
Order By: Relevance
“…The researchers concluded: "Further research will be required to understand whether LF serves as an iron scavenger and may represent a protective factor, or whether it promotes excessive iron buildup leading to oxidative injury in susceptible neurons" [79]. Two recent investigations separately showed that LF might be useful as a non-invasive PD marker, after they discovered that the levels of LF in the saliva and tears of PD patients were higher than those in the same biofluids of the control group [80,81]. Salivary and lacrimal LF levels could be acceptable as PD markers since they are simpler to collect than blood samples and, more importantly, the amounts of LF in both exocrine secretions are substantially larger than the levels of oligomeric alpha-synuclein.…”
Section: Lactoferrin As a Diagnostic Marker For Type 2 Diabetes Diseasesmentioning
confidence: 99%
“…The researchers concluded: "Further research will be required to understand whether LF serves as an iron scavenger and may represent a protective factor, or whether it promotes excessive iron buildup leading to oxidative injury in susceptible neurons" [79]. Two recent investigations separately showed that LF might be useful as a non-invasive PD marker, after they discovered that the levels of LF in the saliva and tears of PD patients were higher than those in the same biofluids of the control group [80,81]. Salivary and lacrimal LF levels could be acceptable as PD markers since they are simpler to collect than blood samples and, more importantly, the amounts of LF in both exocrine secretions are substantially larger than the levels of oligomeric alpha-synuclein.…”
Section: Lactoferrin As a Diagnostic Marker For Type 2 Diabetes Diseasesmentioning
confidence: 99%
“…The analytical methodology established here can be further used to detect and distinguish WT and mutant α-synucleins including A30P, E46K, H50Q, G51D, A53E and A53T, with a precision of single point mutation. It is reported that saliva [33] and tears [34] contain α-synuclein, considering the ease of collection from patients and the composition is less complex than cerebrospinal fluid [35] and blood. [36] Our approach can be readily adopted to report the α-synuclein content and identification of α-synuclein mutation, benefits for more accurate diagnosis of early PD and mutations so as to secure the best window time for specific treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Listuaz gain, malkoak biomarkatzaile-iturri ezagunak dira begiko gaixotasun zein gaixotasun sistemikoetarako, abantaila bereziak eskaintzen Alfa-sinukleina biomarkatzaile gisa Parkinson gaixotasunaren... baitituzte: lagin-bilketa ez da teknika inbaditzailea, eta proteina-konposizioa gero eta hobeto definitua dago. Parkinson gaixotasunean malkoetan α-sinukleina oligomerikoa nabarmen handitzen dela frogatu da, kontrol osasuntsuekin alderatuta [78,79]. Azken ikerketek, ultrasentikorra den entsegu bat erabiliz, frogatu dute α-sinukleina totalaren maila ere areagotuta dagoela Parkinson pazienteen malkoetan [80].…”
Section: Alfa-sinukleinaren Mailak Beste Gorputzeko Fluido Batzuetanunclassified